MiRNA expression can classify pediatric thyroid lesions and increases the diagnostic yield of mutation testing. Issue 6 (20th March 2020) - Franco, Aime T.; Labourier, Emmanuel; Ablordeppey, Kenny Kwabena; Surrey, Lea F.; Mostoufi‐Moab, Sogol; Isaza, Amber; Adzick, N. Scott; Kazahaya, Ken; Kumar, Gyanendra; Bauer, Andrew J.
Abstract: Background: Genetic alterations in multiple cell signaling pathways are involved in the molecular pathogenesis of thyroid cancer. Oncogene mutation testing and gene‐expression profiling are routinely used for the preoperative risk management of adult thyroid nodules. In this study, we evaluated the potential value of miRNA biomarkers for the classification of pediatric thyroid lesions. Procedure: Double‐blind case‐control study with 113 resected pediatric lesions: 66 malignant and 47 benign. Quantitative and qualitative molecular data generated with a 10‐miRNA expression panel (ThyraMIR) and a next‐generation sequencing oncogene panel (ThyGeNEXT) were compared with clinicopathological parameters. Results: miRNAs were differentially expressed in benign versus malignant tumors with distinct expression patterns in different histopathology categories. The 10‐miRNA classifier identified 39 (59%) malignant lesions with 100% specificity. A positive classifier score was associated with lymph node metastasis, extrathyroidal extension and intrathyroidal spread. Genetic alterations associated with increased risk for malignancy were detected in 35 (53%) malignant cases, 20 positive for point mutations in BRAF, HRAS, KRAS, NRAS, PIK3CA, or TERT and 15 positive for gene rearrangements involving ALK, NTRK3, PPARG, or RET . The 10‐miRNA classifier correctly identified 11 mutation‐negative malignant cases. The performance of the combined molecular test was 70% sensitivity and 96% specificity with an area under the curve of 0.924. Conclusions: These data suggest that the regulatory miRNA pathways underlying thyroid tumorigenesis are similar in adults and children. miRNA expression can identify malignant lesions with high specificity, augment the diagnostic yield of mutation testing, and improve the molecular classification of pediatric thyroid nodules.